A Snapshot into Challenges of Policing Rural Zimbabwe - Mutongwizo, Tariro (International Journal of Rural Criminology, 2022)
Policing and security in remote and rural areas are under-resourced and under-researched. The situation is amplified in developing nations such as Zimbabwe, where the most immediate form of local governance for rural dwellers is that of traditional, customary and informal institutions. This research note aims to further discuss policing rural areas in places like Zimbabwe, where patriarchal state structures are entangled with policing. The research note will rely on examples of the key challenges experienced in rural Zimbabwe and engage in a theoretical discussion that paints a picture of policing of the rural developing world. Discussions will centre around how the lack of access to police is exacerbated by distance and the nature of policing, which further excludes individuals based on political affiliation, gender, and poverty. Taking all this into consideration, police-community relations and engagement in rural Zimbabwe will be examined with the aim that the discussion leads to further research on how policing rural communities can better consider the security needs, vulnerabilities, and potential of these communities.